Strangers in barong communication and acculturation of expatriates working in Metro Manila - Cajilig, Pamela G.
"Strangers in Barong : Communication and Acculturation of Expatriates Working in Metro Manila" focused on finding answers to three main problems: how expatriates dealt with the culture gap between their home and host cultures, how an expatriate's use of mass media facilitated the level attained in the acculturation process, and how interpersonal and group interaction influenced the degree to which an expatriate acculturates. Central to this study was Charles Berger's Uncertainty Reduction Theory which asserts that people possess a compulsion to reduce uncertainty about other people by gathering information about them, consequently using that data to predict their behavior. Dimension was then added by William Gudykunst's research on the cross-cultural dimensions of the same theory. He found that although all cultures display the necessity to reduce uncertainty in the early stages of a relationship, it is done so in different manners. Hence, the expatriate living in the Philippines found the necessity to seek information in manners that do not necessarily reflect his home culture. Petty and Cacioppo's Elaboration Likelihood Theory explained how gathered information is processed, as affected by the individual's motivation to acculturate. The information itself is gathered from Mass Media, predicted by the Dependency Theory, and through Interpersonal Interaction, supported by the Social Penetration and Culture General Theory. The proper processing of information lead to a successful sharing of culture between the expatriate and the Filipino. The uncertainty experienced by expatriates in the early stages of acculturation was dealt with by obtaining pertinent information about the culture. Here the Filipino played a key role. Inasmuch as informants read various literature on Philippine culture and traveled to various parts of the country, the Filipino was still the primary source of knowledge regarding the nuances of the culture. The Filipino, whose open and welcoming personality served as an aid in facilitating acculturation, at times was the cause of hindrance due to his indirectness of speech and relaxed working style. Mass media proved to be an excellent source of information for expatriates in terms of providing information about the host culture's present situation / current events. Expatriates also turned to mass media for news regarding their home country. However, media did not play a substantial role in the acculturation process since none of the expatriates were dependent solely on mass media for information. The factor that played the greatest role in determining the level of acculturation an expatriate reached was the amount of interaction he or she had with Filipinos. Often, primary interaction with Filipino took place in a work environment. Nonetheless, such interaction eventually developed into a social relationship due to long term, continued interaction.